2022
DOI: 10.1002/hep4.2004
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic impact of preoperative body composition in perihilar and intrahepatic cholangiocarcinoma

Abstract: Cholangiocarcinoma (CCA) is a rare but highly aggressive malignancy of the biliary system. Although it is amenable to surgical resection in early disease, outcomes are frequently dismal. Here, we investigated the prevalence of body composition (BC) alterations and their prognostic role for surgical patients with intrahepatic (iCCA) and perihilar (pCCA) disease. Patients undergoing curative‐intent surgery for iCCA or pCCA between 2010 and 2019 at University Hospital Aachen were included. Axial computed tomograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 40 publications
2
16
0
Order By: Relevance
“…The most common values and thresholds that could be found in the literature were used for sarcopenia [ 14 , 18 , 39 , 40 ], PMI [ 17 ], myosteatosis [ 14 , 18 , 19 , 24 ], SFI [ 11 ] and visceral obesity [ 41 ]. For the VFI and VSR, no suitable validated thresholds were found.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The most common values and thresholds that could be found in the literature were used for sarcopenia [ 14 , 18 , 39 , 40 ], PMI [ 17 ], myosteatosis [ 14 , 18 , 19 , 24 ], SFI [ 11 ] and visceral obesity [ 41 ]. For the VFI and VSR, no suitable validated thresholds were found.…”
Section: Methodsmentioning
confidence: 99%
“…Sarcopenia, being the most commonly assessed body composition parameter, was found to be a predictor for survival in several malignancies including ovarian cancer, colorectal cancer, cholangiocarcinoma, gastric cancer, pancreatic cancer, prostate cancer, and BC [ 13 , 16 , 21 , 22 , 23 , 24 ]. Similarly, the psoas muscle index and myosteatosis are prognostic factors in different tumor entities including urologic tumors [ 10 , 17 , 25 , 26 , 27 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…As previously described, 9,17 an axial CT image at the level of the third lumbar vertebra from the most recent CT image before surgery was analyzed semi‐automatically with 3D Slicer 18 and the Workstation SlicerCIP extension, body composition module (version 4.10.2). Attenuation values from −29 to 150 Hounsfield units (HU) defined skeletal muscle 19 .…”
Section: Methodsmentioning
confidence: 99%
“…It is currently unclear whether these observations can be translated into oncological settings, where the typical phenotype of cachexia and sarcopenia is the most frequently described alteration. Our group recently reported that sarcopenic obesity may hold value for overall survival in iCCA in a different patient cohort from a German tertiary centre 9 . This publication, despite a lower sample size, showed a high prevalence of body composition pathologies in patients with iCCA and perihilar CCA 9 …”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation